AN OVERVIEW OF DIFFERENT METHODS OF DIGITAL IMAGE COMPRESSION OF MEDICAL IMAGES - Satyawati S.Magar; Dr.Bhavani Sridharan (International Journal of Innovations in Engineering Research and Technology, 2021)
Digital image in raw form which require large amount of storage capacity. Data compression may be performed to facilitate transmission and storage. The type of medical image and the objective of the study will determine the degree of acceptable compression depending on the reconstructed image, to be exactly same as the original or some unidentified loss may be incurred, two techniques for compression exist lossless and lossy. If compression is used, algorithms recommended by the DICOM standard such as wavelet or JPEG-2000 compression methods should be used. This paper also an overview of DWT and DCT implementation because these are the lossy techniques and also introduce Huffman encoding technique which is lossless. At last implement lossless technique so our PSNR and MSE will go better than the old algorithms and due to DWT and DCT we will get good level of compression and maintains the image quality. The types and ratios of compression used for different imaging studies transmitted and stored by the system.